Investigation of the Multiple Imputation Method in Different Missing Ratios and Sample Sizes - Nesrin Alkan; B. Baris Alkan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In many studies, missing data are thereal trouble to researchers. Because the statistical methods are designed forcomplete data sets. Multiple imputation method is developed to solve themissing data problem. The method is also used effectively in some usefulproperties of the Bayes method. If there are missing values in the data set,Bayesian method can be used to prevent the loss of information. In this study,the performance of the multiple imputation method is evaluated by generatingsurvival data with different missing rates and different sample sizes. Also,informative priors and multiple imputation method are used together to preventthe missing information in the variable with missing value.